Democracy in America - Tocqueville, Alexis de (Oxford University Press, 1946)
This new edition is the only one that contains all Tocqueville's writings on America, including the rarely-translated Two Weeks in the Wilderness, an account of Tocqueville's travels in Michigan among the Iroquois, and Excursion to Lake Oneida.